Classical electromagnetic radiation - Heald, Mark A.
"Newly corrected, this highly acclaimed text is suitable for advanced physics courses. The author presents a very accessible macroscopic view of classical electromagnetics that emphasizes integrating electromagnetic theory with physical optics. The survey follows the historical development of physics, culminating in the use of four-vector relativity to fully integrate electricity with magnetism"--